The Demographic and Socio-economic Distribution of Excess Mortality during the 1994 Genocide in Rwanda - de Walque, D.; Verwimp, P. (2012)
This paper studies the demographic consequences of the Rwandan genocide and how the excess mortality due to the conflict was distributed in the population. Data collected by the 2000 Demographic and Health Survey indicate that although there were more deaths across the entire population, adult males were the most likely to die. Using the characteristics of the survey respondent as a proxy for the socio-economic status of the victims' family, the results also show that individuals with an urban or more educated background were more likely to die. The country's loss of human capital is a long-term cost of the genocide that compounds the human tragedies.